Exploration on Space Security Cooperation Path in the Context of East Asian Economic Competition - Li, Xingyi (International Journal of Social Sciences and Public Administration, 2025)
This paper discusses how to promote regional peace and development by strengthening space security cooperation under the background of increasing economic competition in East Asia. First, the paper analyzes the development status of the major economies in East Asia and its impact on the progress of space technology, pointing out that economic competition brings both challenges and opportunities. Next, the study reveals the threats to space security in the region and the existing cooperation mechanisms, and discusses the possible cooperation models and opportunities. Subsequently, a series of concrete paths for building space security cooperation were put forward, including policy suggestions, technical exchanges and the improvement of the legal framework. Finally, the paper summarizes the research results, looks forward to the future space security cooperation in East Asia, and puts forward the direction of further research. The purpose of this study is to provide theoretical support and practical guidance for the long-term stability and prosperity of East Asia.